Penggunaan Media Diorama 3D untuk Meningkatkan Hasil Belajar dan Keaktifan Pembelajaran Peserta didik SD - Nur Sholehah; Desi Zulfiana; Widya Verina Tanjung; Yuniarti Yuniarti; Sabran Sanutra; Nanang Rahman; Syamsuri Syamsuri; Syukri Sani (Universitas Muhammadiyah Mataram, 2025)
Abstract: Science learning in elementary schools requires innovative media that can improve learning outcomes and student activity. This study aims to analyze the effectiveness of using 3D Dioramas in improving learning outcomes and student activity at SD Negeri 1 Banyumulek. The research method uses a quantitative approach with the type of classroom action research (CAR), which is implemented in two cycles. The subjects of the study were 31 fifth grade students, with instruments in the form of multiple choice questions and activity observation sheets. Data collection techniques were test and non-test techniques. The data analysis technique was descriptive quantitative with the average and completeness of the value of the science learning outcomes of the material My Earth Loves My Earth Malang. The results showed an increase in the average score of learning outcomes from 67.74 to 80.65, and the average score of activity from 55.24 to 90.99. Correlation analysis showed that the increase was more influenced by the intervention of 3D Diorama’s media than the initial characteristics of the students. The conclusion of this study is that the use of 3D Diorama media is effective in increasing student activity and learning outcomes in science learning. The implications of this study's results recommend the use of 3D Diorama as an active learning strategy to strengthen conceptual understanding and student participation in elementary schools.Abstrak: Pembelajaran IPAS di sekolah dasar memerlukan media inovatif yang mampu meningkatkan hasil belajar dan keaktifan peserta didik. Penelitian ini bertujuan untuk menganalisis efektivitas penggunaan Diorama 3D dalam meningkatkan hasil belajar dan keaktifan peserta didik di SD Negeri 1 Banyumulek. Metode penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian tindakan kelas (PTK), yang dilaksanakan dalam dua siklus. Subjek penelitian adalah 31 peserta didik kelas V, dengan instrumen berupa soal pilihan ganda dan lembar observasi keaktifan. Teknik pengumpulan data adalah teknik tes dan teknik non tes. Teknik analisis data yaitu secara deskriptif kuantitatif dengan rerata dan ketuntasan nilai hasil belajar IPAS materi Bumiku Sayang Bumiku Malang. Hasil penelitian menunjukkan adanya peningkatan rata-rata skor hasil belajar dari 67,74 menjadi 80,65, dan rata-rata skor keaktifan dari 55,24 menjadi 90,99. Analisis korelasi memperlihatkan bahwa peningkatan tersebut lebih dipengaruhi oleh intervensi media Diorama 3D daripada karakteristik awal peserta didik. Simpulan dari penelitian ini adalah penggunaan media Diorama 3D efektif dalam meningkatkan keaktifan dan hasil belajar peserta didik dalam pembelajaran IPAS. Implikasi hasil penelitian ini merekomendasikan penggunaan Diorama 3D sebagai strategi pembelajaran aktif untuk memperkuat pemahaman konseptual dan partisipasi peserta didik di sekolah dasar.